Managing Child-Friendly Education and Behavioral Counseling to Cultivate Noble Character in Elementary Schools - Sani Nurani; Hanafiah Hanafiah (CV. Media Digital Publikasi Indonesia, 2026)
The cultivation of noble character is a foundational yet increasingly challenged objective of elementary education. A significant gap exists between the aspiration for moral development and the implementation of effective, systemic strategies within schools. This study explores how the integrated management of Child-Friendly Education (CFE) principles and behavioral counseling techniques can strategically foster the noble character of students. This research employed a qualitative methodology with a comparative, multiple-case study design conducted at two distinct Indonesian elementary schools, SDN Tegalsari and SDN Salammulya. Data were gathered through in-depth interviews with principals, teachers, and students; participant observation of school culture and classroom activities; and an extensive analysis of institutional documents. Thematic analysis was rigorously conducted following the interactive model of Miles, Huberman, and Saldaña. The findings reveal a comprehensive management process orchestrated through a cycle of planning, implementation, and evaluation. Planning involved the collaborative integration of specific character goals into school-wide strategic plans (RKAS), guided by both CFE principles and behavioral objectives. Implementation was bifurcated: school-wide strategies fostered a positive culture through teacher modeling and positive habituation, while targeted interventions utilized behavioral techniques like reinforcement systems and individual counseling. Evaluation was managed through continuous observation, non-academic assessments, and reflective institutional meetings, which demonstrated significant improvements in student discipline, empathy, and responsibility. The synergistic management of a child-friendly school environment with systematic behavioral counseling interventions provides an effective and replicable framework for cultivating noble character. This study concludes that this integrated model offers a robust solution for building a generation grounded in positive morals, recommending that school leaders manage both the school's supportive culture and the specific behavioral strategies needed to translate values into observable actions.